Post-occupancy evaluation of state-subsidised housing units in Kayamandi, Stellenbosch - Darkwa, Irene (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Consumer Science)--University of Stellenbosch, 2006.